Egg-shell Treated Oil Palm Fronds (EG-OPF) as Low-Cost Adsorbent for Methylene Blue Removal - Rosalyza Hasan; Nur Aida Farihin Ahliyasah; Chi Cheng Chong; Rohayu Jusoh; Herma Dina Setiabudi (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
A new adsorbent (egg-shell treated oil palm fronds (EG-OPF)) prepared from wastes was evaluated for methylene blue (MB) removal. Optimization among three significant variables (initial concentration (X1), initial pH (X2), and adsorbent dosage (X3)) were executed using response surface methodology (RSM). The most excellent performance was marked at X1 = 291.7 mg/L, X2 = pH 5, and X3 = 1.82 g/L, with MB removal of 80.26 %. The kinetic study was fitted perfectly with the pseudo-second-order model (R2 > 0.990), indicating the chemisorption process. The isotherm study was found to follow the Langmuir isotherm model (R2 = 0.999), with maximal adsorption magnitude of 714.3 mg/g, implying the monolayer adsorption on a homogenous adsorbent surface. The reusability study affirmed the feasibility of EG-OPF in MB removal, credited to its excellent performance during reusability studies. The present study successfully discovered a new low-cost adsorbent (EG-OPF) for MB removal.